Integrated RNA-Seq Analysis Uncovers the Potential Mechanism of the "Kidney Governing Bones" Theory of TCM. (30th March 2022) - Yang, Shuo; Wang, Tiancheng; Zhang, Jingcheng; Leng, Xiangyang; Yao, Baojin
Abstract : Background . As in philosophy of traditional Chinese medicine (TCM), the theory of "kidney governing bones" has been demonstrated by a series of scientific studies. Furthermore, many groups including ours have explored the molecular mechanisms related to bone development, growth, and regeneration using modern biology technologies, such as RNA sequencing (RNA-Seq) and isobaric tags for relative and absolute quantification (ITRAQ), and have demonstrated that the underlying molecular mechanisms were highly consistent with the "kidney governing bones" theory. Objective . Kidney-yang deficiency (YD), as a pathological condition, has a passive effect on the skeleton growth; more specifically, it is a state of skeletal metabolic disorder. However, the exact molecular mechanisms related to the "kidney governing bones" theory under the control of multiple organs and systems are still unknown. Methods . In this study, we performed RNA-Seq analysis to investigate and compare the gene expression patterns of six types of tissue (bone, cartilage, kidney, testicle, thyroid gland, and adrenal gland) from YD rats and normal rats and analyzed the interaction effects controlled by multiple functional genes and signaling pathways between those tissues. Results . Our results showed that, in the state of YD, the functions of bone and cartilage were inhibited. Furthermore, multiple organs involving the reproductive, endocrine, and urinary systems were also investigated, and our results showed that YD could cause dysfunctions of these systems by downregulating multiple functional genes and signaling pathways that positively regulate the homeostasis of these tissues. Conclusion . We ensure that "kidney governing bones" was not a simple change in a single gene but the changes in complex biological networks caused by functional changes in multiple genes. This also coincides with the holistic view of TCM, which holds that the human body itself is an organic whole and the functional activities of each organ coordinate with each other.